Use of the DISCERN tool for evaluating web searches in childhood epilepsy - Cerminara, Caterina; Santarone, Marta Elena; Casarelli, Livia; Curatolo, Paolo; El Malhany, Nadia (Epilepsy & behavior, 2014)
Epilepsy is an important cause of neurological disability in children. Nowadays, an increasing number of parents or caregivers use the Internet as a source of health information concerning symptoms, therapy, and prognosis of epilepsy occurring during childhood. Therefore, high-quality websites are necessary to satisfy this request. Using the DISCERN tool, we evaluated online information on childhood epilepsy provided by the first 50 links displayed on the Google search engine. The same links were evaluated by a team of pediatric neurologists (PNs) and by a lay subject (LS). The evaluation performed by the PNs found out that only 9.6% of the websites showed good reliability, that only 7.2% of the websites had a good quality of information on treatment choices, and that only 21.5% of the websites showed good overall quality of the content. With regard to the evaluation performed by the neutral subject, it was found that 21.4% of the websites showed good reliability, that 59.5% of the websites showed poor quality of information on treatment choices, and that only 2% of the websites showed good overall quality of the content. Our conclusion is that online information about childhood epilepsy still lacks reliability, accuracy, and relevance as well as fails to provide a thorough review of treatment choices. •Internet is one of the most common health information sources.•Evaluation of websites by pediatric neurologists and by a neutral subject using the DISCERN tool•Online searches concerning childhood epilepsy are not yet completely reliable.•Sites lack good relevance, description of treatment options, and accuracy of data.